Molding and making dental prosthesis on implants: Case report (Research, Society and Development, 2024)
Currently, with the advancement of implant dentistry in dentistry and the great search for patients with the intention of replacing one or more teeth, it has become increasingly frequent. Since, with dental implants, the prostheses are completely fixed on them, which brings them in a harmonious way and is close to a natural tooth today. The objective of this work is to describe a case report of prosthetic construction after the installation of dental implants. The scarring was removed and the mini-abutment and transfer components were installed to faithfully copy the patient's dental implants, followed by the prosthetic installation of a protocol-type complete and total fixed prosthesis. Fixed prostheses on implants emerged with the aim of improving the stability of other prostheses, enabling the patient to once again achieve chewing function and dental aesthetics that resemble natural teeth.